THE PRESENCE OF UNCERTAINTY IN SPORT - A LITERATURE REVIEW - Gergely CSURILLA; Tamás STERBENZ (Cluj University Press, 2022)
The notions of luck, risk, noise, and uncertainty could be often read in sports-related literature. However, there was not published a study so far that attempts to summarize the differences and similarities among them. In this paper, we aim to review the most influential papers, books carried out in relation to these concepts. As the topic of uncertainty in sports literature is quite diverse, therefore, we followed a review method aiming for theory development instead of a systematic review. Using an alternative review methodology enabled us to organize the existing theories in three main categories based on who is affected by the uncertainty: spectator, athlete, and sport level. The main finding of our paper is that uncertainty has distinct consequences at different levels. The demand for sport requires a certain level of uncertainty from the fans' point of view to maintain the uncertainty of outcome. Athletes, on the other hand, are adversely affected by uncertainty. In sport level, the impact of the uncertainty on the results should be carefully managed. The topic of uncertainty in sport is characterized by contradiction. From the perspective of spectators, an adequate amount of uncertainty is required to maintain an interest in the sport. However, the athletes do not prefer uncertainty which they could not influence. It is up to decision-makers in sport to establish such regulation which they can balance with the uncertainty to maintain the interest of spectators and to encourage athletes for the best performance. Received: 2022 January 19; Revised: 2022 March 03; Accepted: 2022 March 03; Available online: 2022 May 5; Available print: 2022 May 30.